Digital Transformation in Educational Human Resource Management: A Study of HRIS System Implementation - Yancis, Yancis (International Journal on Advanced Science, Education, and Religion, 2025)
The application of information technology in human resource management has become a strategic necessity in the education sector. This study aims to in-depth assess the readiness of educational institutions to adopt Human Resource Information Systems (HRIS) and analyze the factors influencing their successful implementation. The study employed a qualitative approach with a systematic literature review of scientific publications from the past ten years. Content analysis was used to identify themes, patterns, and relationships between relevant concepts. The study's findings indicate that successful HRIS implementation is influenced by top management support, staff digital competence, technological infrastructure readiness, and the effectiveness of training and an organizational culture that supports change. HRIS has been shown to improve administrative efficiency, decision-making quality, personnel data accuracy, and transparency in HR management. The study also highlights the role of transformational leadership and the importance of change management strategies in overcoming organizational resistance. The implications of this study indicate that effective HRIS implementation requires a holistic approach encompassing technical, structural, and cultural aspects. These findings provide an important contribution to the development of technology-based HR management policies and practices in the education sector.